IMPACT OF COVID-19 ON THE REVERSE MIGRATION OF THE WORKFORCE: A STUDY OF UTTARAKHAND (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The study aims to identify the dimensions responsible for the reverse migration of the workforce during the period of the Covid-19 pandemic. The dimensions identified in the study include health and safety, loss of employment, and emotional factor. The exploratory research is based on both the qualitative and quantitative approaches. Primary data has been gathered through telephonic and face-to-face interviews using a structured questionnaire based on a Seven-Point Likert scale. The data has been analysed by using statistical techniques- exploratory factor analysis and multiple regression. Findings indicated that there has been a significant impact of identified factors on the migration of the workforce. It created a challenging situation to the government to make suitable arrangements for the workforces who have come back to their native State.